The evolution of Vaccination Week in the Americas - Ropero Alvarez, Alba Maria (Rev Panam Salud Publica, 2017)
This report covers the background and evolution of Vaccination Week in the Americas (VWA), an initiative that started as a coordinated response to a 2002 measles outbreak in Colombia and Venezuela, and evolved into the model for other regions and World Immunization Week (WIW). VWA focuses on the work of national immunization programs, with special efforts to reach the unreached. This paper offers examples of how countries have leveraged VWA to implement a diverse array of vaccination activities, strengthening overall health services by integrating with other preventive health interventions, and bolstering “Pan-Americanism” and health diplomacy. The opportunities offered by this global initiative were clearly demonstrated in April 2016 when the successful global switch from the trivalent oral polio vaccine to the bivalent vaccine was synchronized with WIW. Going forward, VWA and WIW can help close the gaps in access to immunization and other health services, contributing to achieve universal health coverage.